Expediente (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
In this issue we present the Urdimento Editorial Team, made up of the Editorial Board, Associate Editors, Thematic Dossier Editors, Scientific and Editorial Board, and the Board of Reviewers working on this issue of Urdimento. We also present the Editorial Support Team.
Keywords: expediente; editorial board; urdimento